A medical magnesium rare earth alloy powder and its preparation method and application

By preparing medical magnesium rare earth alloy powder with reasonable contents of Sc, Zr, and Y, and using additive manufacturing and high-temperature oxidation heat treatment processes to form a dense rare earth oxide protective layer, the problem of excessive degradation rate and poor performance of magnesium alloy bone implants is solved. Optimize the problem and achieve efficient mechanical support and corrosion resistance.

CN118241093BActive Publication Date: 2025-01-21PEKING UNIVERSITY THIRD HOSPITAL (THE THIRD CLINICAL MEDICAL SCHOOL OF PEKING UNIVERSITY)

Patent Information

Application Number
CN202410228060.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2025-01-21
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

When existing magnesium alloy powders are used to produce bone implants with additive manufacturing, the degradation rate is too fast, the biocompatibility is reduced, and the corrosion resistance and antibacterial properties are poor, which cannot meet the performance requirements of bone implants.

Method used

Provides a medical magnesium rare earth alloy powder with the composition of Sc: 0.5-2.75%, Zr: 0-0.5%, Y: 4-7%, prepared through vacuum smelting and atomization powdering processes, combined with additive manufacturing and high-temperature oxidation Heat treatment to form a dense rare earth oxide protective layer to improve corrosion resistance and mechanical support.

Benefits of technology

It achieves a good combination of mechanical strength and corrosion resistance of magnesium alloy bone implants, avoids biological hazards, and provides continuous mechanical support. The number of days of mechanical support is ≥85 days, which is better than the performance requirements of my country's medical industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118241093B_ABST
    Figure CN118241093B_ABST
Patent Text Reader

Abstract

The present invention relates to a medical magnesium rare earth alloy powder and a preparation method and application thereof, belonging to the technical field of metal additive manufacturing. It is used to solve the problem that the existing magnesium alloy powder is used for additive manufacturing of formed bone implants, which will lead to excessive degradation rate of magnesium alloy bone implants, decreased biocompatibility, poor corrosion resistance and antibacterial properties, and fail to meet the performance requirements of bone implants. A medical magnesium rare earth alloy powder, the composition by weight percentage is: Sc: 0.5-2.75%, Zr: 0-0.5%, Y: 4-7%, and the rest is Mg and non-removable impurity elements. The magnesium alloy powder of the present invention has high purity, few impurities, slight surface oxidation, is suitable for laser additive manufacturing, has no obvious component deviation, and is controllable in composition; the magnesium alloy bone implant obtained by additive manufacturing has good corrosion resistance, can continuously provide mechanical support, and the number of mechanical support days is ≥85 days, which is better than the performance requirements of bone implants in my country's medical industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal additive manufacturing, and in particular to a medical magnesium rare earth alloy powder and a preparation method and application thereof. Background Art

[0002] Because the spatial shape of human bones is relatively complex, alloy powder is used to form bone implants. If general forming processes (such as casting, forging, etc.) are adopted, there are problems such as complex preparation process, low manufacturing precision, long manufacturing cycle and high production cost.

[0003] Additive manufacturing can achieve precise manufacturing of bone defect prostheses that match bone anatomy and have microporous connectivity by printing digitally designed materials layer by layer. At present, orthopedic clinical additive manufacturing implant repair materials are mainly based on bio-inert metal titanium and its alloys, which are the main choice for repairing and fixing segmental bone defects in load-bearing parts. However, titanium alloy prostheses are non-degradable and cannot be used to fill and repair collapsed bone defects in the peri-articular area.

[0004] Magnesium and magnesium alloys are currently considered to be the most prominent biodegradable metals due to their mechanical properties that match those of human bones, their complete degradation in body fluids, and their ability to promote bone integration. Additive manufacturing can cleverly use computer-aided design to design implant materials / devices with complex structures based on patient-specific anatomical data, and quickly manufacture these materials / devices within a reasonable range of dimensional accuracy. Compared with traditionally manufactured magnesium alloy stents, they have superior mechanical and biological properties. Therefore, the current research trend is to develop ideal biodegradable magnesium-based devices for precision treatment through additive manufacturing methods.

[0005] The existing magnesium alloy powders used in the preparation of magnesium alloy bone implants by additive manufacturing methods have the following problems: 1. Most of the existing magnesium alloy powders are commercial casting grade magnesium alloys. There is no magnesium alloy powder specifically used for medical additive manufacturing, which cannot match the additive manufacturing process characteristics and medical implant requirements; 2. The existing magnesium alloy powders are mostly used in industrial fields such as aviation, and have a large number of metal components added. If they are used for additive manufacturing of magnesium alloy bone implants, the degradation rate of the magnesium alloy bone implants will be too fast, and they will not be able to provide the dynamic mechanical support required for bone healing throughout the entire bone healing cycle; at the same time, their biocompatibility will also decrease; 3. The existing magnesium alloy powders used for additive manufacturing of magnesium alloy bone implants have poor corrosion resistance and antibacterial properties. Taking WE43 magnesium alloy as an example, this mixed multi-component rare earth magnesium alloy has obtained CE certification and is used in clinical practice. However, this multi-component alloy requires a large amount of rare earth elements (8wt%) to achieve a good combination of mechanical strength and corrosion resistance, and the addition of a large amount of rare earth elements may bring about the problem of biological hazards; on the other hand, related magnesium alloys represented by WE43 are usually made by casting or die-casting, and accelerated degradation occurs during the additive manufacturing process. The solid solution solubility of the rare earth element neodymium (Nd) is less than 2.5wt%. Therefore, during the high-temperature laser additive manufacturing process, Nd is easily precipitated to form a second phase, forming a Mg-RE compound, which causes galvanic corrosion in the magnesium alloy.

[0006] Therefore, it is necessary to improve the magnesium alloy powder material so that it can be used in additive manufacturing of bone implants and form bone implants of complex shapes while meeting their performance requirements. Summary of the invention

[0007] In view of the above analysis, the embodiments of the present invention aim to provide a medical magnesium rare earth alloy powder and a preparation method and application thereof, so as to solve at least one of the following technical problems: 1. Existing magnesium alloy powder cannot be used for additive manufacturing of bone implants; 2. Forcibly using existing magnesium alloy powder for additive manufacturing of bone implants will cause the magnesium alloy bone implant to degrade too quickly, reduce biocompatibility, and have poor corrosion resistance and antibacterial properties, which does not meet the performance requirements of bone implants.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] The invention provides a medical magnesium rare earth alloy powder, the components of which are as follows by weight percentage: Sc: 0.5-2.75%, Zr: 0-0.5%, Y: 4-7%, and the rest are Mg and unremovable impurity elements.

[0010] The present invention also provides a method for preparing medical magnesium rare earth alloy powder, which is used to prepare the medical magnesium rare earth alloy powder according to claim 1, comprising:

[0011] Step 1: weighing pure metal ingots and / or high-purity alloy ingots according to the magnesium alloy composition ratio, wherein the pure metal ingot is a Mg ingot, and the high-purity alloy ingot includes a Mg-Y master alloy, a Mg-Sc master alloy, and a Mg-Zr master alloy;

[0012] Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot;

[0013] Step 3: Detect the composition of the master alloy ingot, remove dirt or oxide layer on the surface of the master alloy ingot by pickling or mechanical grinding, and remelt the master alloy ingot again to obtain a master alloy ingot melt;

[0014] Step 4: atomizing the master alloy ingot melt to obtain a first pre-alloyed powder;

[0015] Step 5: Sieve the first pre-alloyed powder through a sieve to obtain a second pre-alloyed powder that meets the size and shape requirements;

[0016] Step 6: vacuum drying the second pre-alloyed powder to obtain magnesium alloy powder, and vacuum packaging it.

[0017] Furthermore, in step 2, during the vacuum melting process, the heating temperature is 750-800° C., the holding time is 8-12 min, and the stirring rate is 30-35 r / min.

[0018] Furthermore, in step 3, the remelting temperature is 700-800°C.

[0019] Furthermore, in step 4, the atomization powder making is an argon protection combined atomization method, the atomization temperature is 750-800°C, the atomization pressure is 30-50KPa, the nozzle size is 5-10mm, and the atomizer speed is 55000-65000r / min.

[0020] The present invention also provides the use of the medical magnesium rare earth alloy powder or the medical magnesium rare earth alloy powder prepared by the above preparation method in the manufacture of magnesium alloy bone implants.

[0021] The present invention also provides a medical bone implant material, which is prepared from the above-mentioned medical magnesium rare earth alloy powder or the medical magnesium rare earth alloy powder prepared by the above-mentioned preparation method.

[0022] The present invention also provides a method for preparing a medical bone implant material, which is used to prepare the above-mentioned medical bone implant material, including additive manufacturing and high-temperature oxidation heat treatment, wherein the high-temperature oxidation heat treatment includes:

[0023] S1: Additively manufactured magnesium alloy bone implant material cooled to room temperature and pickled;

[0024] S2: After pickling, ultrasonic cleaning is performed to remove residual acid on the surface, followed by drying for 24h-48h;

[0025] S3: After drying, HTO treatment is performed, the thermal oxidation temperature is 500-530°C, and the thermal oxidation time is 6-18h.

[0026] Furthermore, the additive manufacturing is selective laser melting, and the parameters are: scanning power is 600-800W, scanning speed is 500-600mm / s, powder thickness is 18-22μm, and scanning spacing is 60-80μm.

[0027] The present invention also provides a medical bone implant, which is prepared by using the above medical bone implant material or by the above preparation method.

[0028] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0029] 1. The alloy powder provided by the present invention has a simple composition, which can avoid the problem that the magnesium alloy bone implant will degrade too quickly when more metal components are added, and will not be able to provide the dynamic mechanical support required for bone healing during the entire bone healing cycle.

[0030] 2. The alloy powder provided by the present invention can achieve a good combination of mechanical strength and corrosion resistance through reasonable matching of components and contents, avoiding the trouble of biological hazards that may be caused by the addition of a large amount of rare earth elements.

[0031] 3. The present invention controls the parameters in the powder making process to ensure that the melt is atomized and powdered in a low-oxygen, low-humidity inert gas atmosphere, thereby avoiding powder aggregation / agglomeration and contamination caused by electrostatic attraction, moisture absorption, impurity introduction, and surface oxidation in conventional ball milling, and the powder performance is stable.

[0032] 4. The preparation process of the magnesium alloy powder of the present invention controls impurities throughout the entire process, and the obtained magnesium alloy powder has high purity, which improves the corrosion resistance of printed bone implants and is suitable for medical applications. The powder of the present invention is sealed and can be used immediately after opening without the need for heating and drying in advance, and the product is simple and convenient to use.

[0033] 5. The magnesium alloy powder of the present invention has high purity, few impurities, and slight surface oxidation, and is suitable for laser additive manufacturing. During the laser additive manufacturing process, little magnesium element evaporates, and the composition of the additively manufactured magnesium alloy is consistent with the powder composition, without obvious composition deviation, and the composition is controllable.

[0034] 6. The magnesium alloy powder of the present invention has good fluidity after being melted by laser treatment and can be spread quickly, and the finished parts printed by additive manufacturing are dense and defect-free.

[0035] 7. The magnesium alloy powder of the present invention is manufactured by additive manufacturing to obtain a magnesium alloy bone implant having a dense rare earth oxide protective layer (oxide layer + migration layer), which is composed of Sc2O3 and Y2O3 in the outer layer; wherein the PBR values ​​of Y2O3 and Sc2O3 are between 1 and 2, and the oxide layer structure is relatively dense, which can isolate the magnesium matrix from the contact with the corrosive medium, thereby greatly improving the corrosion resistance of the additively manufactured magnesium alloy bone implant.

[0036] 8. The magnesium alloy bone implant obtained by additive manufacturing of the magnesium alloy powder of the present invention has good corrosion resistance and can continuously provide mechanical support for ≥85 days, which is better than the performance requirements of bone implants in my country's medical industry.

[0037] 9. The magnesium alloy bone implant obtained by additive manufacturing and high-temperature oxidation heat treatment of the magnesium alloy powder of the present invention has a compressive yield strength of ≥40MPa, a compressive ultimate strength of ≥60MPa, and a Young's modulus of ≥6Gpa.

[0038] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0040] Figure 1 The microstructure of the EDS cross section of the magnesium alloy bone implant in Example 1;

[0041] Figure 2 Cell scratch images of the magnesium alloy bone implant of Example 1 and the bone implant formed by WE43 alloy under the same conditions after 0h and 24h;

[0042] Figure 3 The figure is a quantitative analysis of the cell scratch migration ability of the magnesium alloy bone implant of Example 1 and the bone implant formed by WE43 alloy under the same conditions after 0h and 24h;

[0043] Figure 4 The bacterial species in the extracts of the magnesium alloy bone implant of Example 1 and the bone implant formed by WE43 alloy under the same conditions after 0h and 24h.

[0044] Reference numerals: 1 - oxidation layer; 2 - migration layer; 3 - central layer. DETAILED DESCRIPTION

[0045] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0046] The invention provides a medical magnesium rare earth alloy powder, the components of which are as follows by weight percentage: Sc: 0.5-2.75%, Zr: 0-0.5%, Y: 4-7%, and the rest are Mg and unremovable impurity elements.

[0047] The reasons for limiting the composition ratio of magnesium rare earth alloy powder for medical use of the present invention are explained below. Only % is used to represent the weight percentage in the composition:

[0048] Sc: The Sc element can provide mechanical properties and corrosion resistance of magnesium alloy powder after forming the magnesium matrix; the Sc element has high solid solubility and good biocompatibility in the magnesium matrix, and its biocompatibility is significantly higher than that of other rare earth elements; at the same time, the addition of the Sc element significantly increases the in vitro antibacterial ability of the magnesium matrix, with a broad antibacterial spectrum, which can reduce bacterial colonization in the prosthesis; the Sc element, as a metamorphic element, can reduce the tendency of magnesium alloy to crack during printing, so that the magnesium alloy has good formability, and the Sc content is controlled at 0.5-2.75%.

[0049] Y: Yttrium has a high solid solubility in magnesium. Together with other rare earth elements, it can improve the high-temperature tensile strength and creep properties of magnesium alloys and improve corrosion behavior. The Y content is controlled at 4-7%.

[0050] Zr: Zirconium can refine grains, reduce thermal cracking tendency, and improve the mechanical properties and heat resistance of the alloy; the Zr content is controlled at 0-0.5%.

[0051] The present invention also provides a method for preparing medical magnesium rare earth alloy powder, which is used to prepare the medical magnesium rare earth alloy powder, comprising the following steps:

[0052] Step 1: weigh pure metal ingots and / or high-purity alloy ingots according to the composition ratio of the magnesium alloy;

[0053] Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot;

[0054] Step 3: Detect the composition of the master alloy ingot, remove dirt or oxide layer on the surface of the master alloy ingot by pickling or mechanical grinding, and remelt the master alloy ingot again to obtain a master alloy ingot melt;

[0055] Step 4: atomizing the master alloy ingot melt to obtain a first pre-alloyed powder;

[0056] Step 5: Sieve the first pre-alloyed powder through a sieve to obtain a second pre-alloyed powder that meets the size and shape requirements;

[0057] Step 6: vacuum drying the second pre-alloyed powder to obtain magnesium alloy powder, and vacuum packaging it.

[0058] Specifically, in step 1, pure metal ingots and / or high-purity alloy ingots are weighed according to the composition ratio, wherein the pure metal ingots are Mg ingots, and the high-purity alloy ingots include Mg-Y master alloys, Mg-Sc master alloys, and Mg-Zr master alloys, and are set aside. The purity of the Mg ingots, Mg-Y master alloys, Mg-Sc master alloys, and Mg-Zr master alloys is ≥99.99%.

[0059] Specifically, in step 2, the vacuum melting process is:

[0060] Put the weighed Mg ingot, Mg-Y master alloy, Mg-Sc master alloy and Mg-Zr master alloy into the tantalum crucible of the vacuum medium frequency induction furnace and evacuate the furnace. When the vacuum degree is less than 1*10 -2 Pa, start heating and fill in inert gas as protective atmosphere, heat and stir the melt, and after it is completely melted, pour the uniform melt into the graphite mold, and obtain the intermediate alloy ingot after cooling with the furnace. The inert gas is one of high-purity argon or CO2+SF6 mixed gas; the heating temperature is 750-800℃, the insulation time is 8-12min, and the stirring rate is 30-35r / min; the graphite mold is preheated to 150-200℃ in advance to avoid the "thermal shock" of high-temperature liquid metal to the mold and extend the service life of the mold. The pouring temperature is 750-850℃.

[0061] It should be noted that melting and pouring under the protection of inert gas can reduce element loss, alloy oxidation and inclusions. Using high-purity graphite molds for melting and pouring can reduce the introduction of impurities and control the content of impurity elements such as Fe, Cu, Ni, Co, Be, and Al that are unfavorable to the corrosion performance of magnesium alloys to make their content less than 100ppm. After the alloy is poured, it is tested to ensure that the content of impurity elements is less than 100ppm. After passing the test, the subsequent process is carried out.

[0062] Specifically, in step 3, the composition of the intermediate alloy ingot is detected to determine that the composition is qualified and meets the requirements of the present invention, then the dirt or oxide layer on the surface of the intermediate alloy ingot is removed by pickling or mechanical grinding, and the intermediate alloy ingot is remelted again to obtain an intermediate alloy ingot melt; the remelting temperature is 700-800°C.

[0063] Specifically, in step 4, the master alloy ingot melt is atomized to obtain alloy powder; the atomization is an argon protection combined atomization method, before atomization, the argon is dehydrated / dried and deoxygenated, and then introduced into the atomization bin to ensure that the oxygen content and humidity of the environment in which the melt is atomized are both lower than 10ppm, so as to avoid / reduce oxidation and corrosion of the powder; during the atomization process, the high-temperature melt is ejected through the narrow nozzle of the atomization device, falls on the high-speed rotating atomizer, and is rapidly split into fine metal droplets under the action of centrifugal force, and then impacted with low-temperature and high-pressure argon gas, so that the metal droplets are rapidly cooled and solidified, and a pre-alloyed powder with good sphericity, uniform particle size distribution, good surface quality (no oxidation / slight oxidation) and high dispersion is obtained. Wherein, the atomization temperature is 750-800℃, the atomization pressure is 30-50KPa, the nozzle size is 5-10mm, and the atomizer speed is 55000-65000r / min.

[0064] Specifically, in step 5, the first pre-alloyed powder is sieved through 100 mesh and 250 mesh sieves under the protection of inert gas to obtain a second pre-alloyed powder that meets the size and shape requirements. The average particle size of the second pre-alloyed powder is 10-150 μm, the powder shape is nearly spherical or spherical, and the sphericity rate is greater than 90%, thereby ensuring the fluidity of the powder; preferably, the average particle size of the pre-alloyed powder is 20-60 μm.

[0065] The present invention also provides a medical bone implant material, which is made from the above-mentioned magnesium alloy powder or magnesium alloy powder prepared by the preparation method. The preparation method of the medical bone implant material includes additive manufacturing and high-temperature oxidation heat treatment of the magnesium alloy powder.

[0066] Specifically, the additive manufacturing generally forms magnesium alloy powder into the shape of a bone implant by selective laser melting (SLM). The additive manufacturing parameters are: scanning power of 600-800W, scanning speed of 500-600mm / s, powder thickness of 18-22μm, and scanning spacing of 60-80μm. Before additive manufacturing, the substrate of the selective laser melting equipment is preheated at a preheating temperature of 180-220℃.

[0067] It should be noted that magnesium alloy powder melts during the additive manufacturing process, and tiny melts flow and spread, connecting with each other, and the additive manufacturing print is obtained by cooling and repeating the above process. The present invention reduces the oxidation and inclusion of the substrate through the precise design of the alloy composition and the precise control of the process parameters during the preparation of the magnesium alloy powder, and controls the atmosphere, environmental oxygen content and humidity during the atomization powder making stage, effectively avoiding / reducing the oxidation of the magnesium alloy powder, thereby improving the performance of the prepared magnesium alloy bone implant.

[0068] The rare earth elements Y and Sc used in the present invention have boiling points of 4300° C. and 2831° C. respectively, low saturated vapor pressure, low evaporation rate, less evaporation loss in the process of atomization powder making and additive manufacturing, non-flammable, and reduced smoke generation. The magnesium alloy bone implant finally obtained by additive manufacturing has a composition that is substantially consistent with that of the initial magnesium alloy powder, and it is easy to obtain a high-molding quality additively manufactured magnesium alloy bone implant with a predetermined composition and a target structure.

[0069] The addition of Sc and Y rare earth elements can refine the grains and improve the corrosion resistance and mechanical strength of magnesium alloy bone implants. At the same time, after obtaining the finished product of additively manufactured magnesium alloy bone implants, the integrated high-temperature oxidation heat treatment process can form a three-layer organizational structure from top to bottom on the surface of magnesium alloy bone implants, namely, the oxide layer, the migration layer and the magnesium matrix layer.

[0070] Specifically, the integrated high temperature oxidation heat treatment process includes the following steps:

[0071] S1: After the finished product of additively manufactured magnesium alloy bone implant is cooled to room temperature, it is pickled;

[0072] Specifically, after the finished product of the additively manufactured magnesium alloy bone implant is cooled to room temperature, it is placed in a dissolving solution for pickling treatment to reduce the residual powder on the surface. The entire pickling process is cooled in a water bath to prevent the acid solution from boiling due to excessive heat released by pickling. The dissolving solution includes a volume concentration of 5%-10% HNO3, 5%-10% HCl and 80-90% alcohol; the pickling time is 1-3 minutes; after the pickling is completed, the printed sample will reach the set porosity (60%-80%).

[0073] S2: After pickling, the finished product of the additively manufactured magnesium alloy bone implant is ultrasonically treated twice with alcohol to wash away the residual acid on the surface, and then placed in a drying oven for drying for 24h-48h;

[0074] S3: After drying, the finished additively manufactured magnesium alloy bone implant is placed in a muffle furnace for HTO treatment, with a thermal oxidation temperature of 500-530°C and a thermal oxidation time of 6-18h.

[0075] Specifically, in order to ensure the uniformity of the HTO treatment, the dried additively manufactured magnesium alloy bone implant product is placed on a bracket made of wire mesh, and the bracket is placed in a muffle furnace for HTO treatment.

[0076] It should be noted that, through energy spectrum analysis, it can be seen that the dense rare earth oxide protective layer (oxide layer + migration layer) is composed of Sc2O3 and Y2O3 in the outer layer; the PBR values ​​of Y2O3 and Sc2O3 are between 1 and 2, and the oxide layer structure is relatively dense, which can isolate the contact between the magnesium matrix and the corrosive medium, greatly improving the corrosion resistance of the additively manufactured magnesium alloy bone implant, that is, the two elements Y and Sc inside the magnesium alloy bone implant can be migrated to the surface of the magnesium alloy bone implant, and the formed oxide layer preferentially contacts with corrosive media such as body fluids, reducing the contact between the magnesium alloy bone implant and the body fluid, improving the corrosion resistance of the magnesium alloy bone implant, and reducing Mg 24 The formation of secondary phases such as Y5. Among them, the Sc element has high solid solubility and good biocompatibility in magnesium alloy bone implants, and its biocompatibility is significantly higher than that of other rare earth elements; at the same time, the addition of the Sc element significantly increases the in vitro antibacterial ability of magnesium alloy bone implants, with a broad antibacterial spectrum, which can reduce bacterial colonization in the prosthesis; at the same time, the dense rare earth oxide protective layer (Sc2O3 and Y2O3) formed under high-temperature oxidation heat treatment has a broad-spectrum antibacterial effect, which can effectively kill Staphylococcus aureus and Escherichia coli in vitro and prevent orthopedic implant infection.

[0077] The performance requirements of bone implants in my country are generally as follows: depending on the different fracture sites and degree of bone defects, the mechanical support days provided by the bone implant should be maintained at 80-85 days. The magnesium alloy powder of the present invention is used in the bone implants formed by additive manufacturing, which has good corrosion resistance and can continuously provide mechanical support. The mechanical support days are ≥85 days, which is better than the performance requirements of bone implants in my country's medical industry.

[0078] Example 1

[0079] A medical magnesium rare earth alloy powder comprises the following components by weight percentage: Sc: 2.25%, Zr: 0.6%, Y: 4.00%, and the rest are Mg and impurity elements that cannot be removed.

[0080] Prepared by the following steps:

[0081] Step 1: weigh pure metal ingots and / or high-purity alloy ingots according to the composition ratio of the magnesium alloy;

[0082] According to the composition ratio, Mg ingots, Mg-Zr ingots, Mg-30Sc ingots, and Mg-20Y ingots with a purity of more than 99.99% were weighed, with a total weight of 50 kg; including 0.85 kg of Mg-30Zr, 4.5 kg of Mg-30Sc, 15 kg of Mg-20Y, and 29.65 kg of Mg.

[0083] Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot;

[0084] Put the weighed Mg ingot, Mg-20Y master alloy, Mg-30Sc master alloy and Mg-Zr master alloy into the tantalum crucible of the vacuum medium frequency induction furnace and evacuate the furnace. When the vacuum degree is less than 1*10 -2 Pa, start heating and fill with high-purity argon as a protective atmosphere, heat at 780°C, keep warm for 10 min, stir the melt with a graphite stirring paddle at a stirring rate of 30 rpm / min; after complete melting, pour the uniform melt into a graphite mold preheated to 200°C at a pouring temperature of 800°C, and obtain an intermediate alloy ingot after cooling with the furnace.

[0085] Step 3: Detect the composition of the master alloy ingot to ensure that the content of impurity elements such as Fe, Cu, Ni, Co, Be, and Al is less than 100ppm, then pickle or mechanically polish to remove dirt or oxide layer on the surface of the master alloy ingot, and remelt the master alloy ingot at 800°C to obtain a master alloy ingot melt;

[0086] Step 4: The master alloy ingot melt is powdered by atomization to obtain pre-alloyed powder;

[0087] The atomization powder making method is argon atomization. Before atomization, the argon is dehydrated / dried and deoxygenated. Argon is protected by combined atomization and then introduced into the atomization chamber to ensure that the oxygen content and humidity of the environment in which the melt is atomized are both lower than 10ppm.

[0088] The atomization temperature is 800°C, the atomization pressure is 35KPa, the nozzle size is 6mm, and the atomization speed is 60000rpm / min.

[0089] Step 5: The pre-alloyed powder is sieved through 100 mesh and 250 mesh sieves to obtain a pre-alloyed powder with an average particle size of 45 μm and a nearly spherical or spherical shape;

[0090] The prepared pre-alloyed powder has high purity, few impurities, and slight surface oxidation, and is suitable for laser additive manufacturing. During the laser additive manufacturing process, little magnesium evaporates, the composition of the additively manufactured magnesium alloy is consistent with the powder composition, there is no obvious composition deviation, and the composition is controllable. After laser processing and melting, it has good fluidity and can be spread quickly. The finished products printed by additive manufacturing are dense and defect-free.

[0091] The above pre-alloyed powder was used in the additive manufacturing process and formed into the shape of the bone implant by selective laser melting (SLM). The additive manufacturing parameters were: scanning power of 500W, scanning speed of 600mm / s, powder thickness of 20μm, and scanning spacing of 70μm. Before additive manufacturing, the substrate of the selective laser melting equipment was preheated at a preheating temperature of 200℃.

[0092] The magnesium alloy bone implant obtained by additive manufacturing is subjected to an integrated high-temperature oxidation heat treatment to obtain a final magnesium alloy bone implant, wherein the integrated high-temperature oxidation heat treatment process comprises the following steps:

[0093] S1: After the finished product of additively manufactured magnesium alloy bone implant is cooled to room temperature, it is pickled;

[0094] After the finished additively manufactured magnesium alloy bone implant is cooled to room temperature, it is placed in a dissolving solution for pickling, and the entire pickling process is cooled in a water bath; wherein the dissolving solution includes 5% HNO3, 5% HCl and 90% alcohol by volume; and the pickling time is 3 minutes.

[0095] S2: After the pickling is completed, the finished product of the additively manufactured magnesium alloy bone implant is ultrasonically treated twice with alcohol to wash away the residual acid on the surface, and then placed in a drying oven for drying for 24 hours;

[0096] S3: After drying, the finished product of the additively manufactured magnesium alloy bone implant is placed in a muffle furnace for HTO treatment, with a thermal oxidation temperature of 525°C and a thermal oxidation time of 8 h.

[0097] Through energy spectrum analysis of the magnesium alloy bone implant after high temperature oxidation heat treatment in this embodiment, the surface of the magnesium alloy bone implant forms a three-layer structure from top to bottom, which are an oxide layer, a migration layer and a magnesium matrix layer. Figure 1 shown.

[0098] The dense rare earth oxide protective layer (oxide layer + migration layer) is composed of Sc2O3 and Y2O3 in the outer layer; the PBR values ​​of Y2O3 and Sc2O3 are between 1 and 2, and the oxide layer structure is relatively dense, which can isolate the contact between the magnesium matrix and the corrosive medium, greatly improving the corrosion resistance of the additively manufactured magnesium alloy bone implant. In other words, the two elements Y and Sc inside the magnesium alloy bone implant can be migrated to the surface of the magnesium alloy bone implant, and the formed oxide layer preferentially contacts with corrosive media such as body fluids, reducing the contact between the magnesium alloy bone implant and the body fluid, improving the corrosion resistance of the magnesium alloy bone implant, and reducing Mg 24 The formation of secondary phases such as Y5. Among them, the Sc element has high solid solubility and good biocompatibility in magnesium alloy bone implants, and its biocompatibility is significantly higher than that of other rare earth elements; at the same time, the addition of the Sc element significantly increases the in vitro antibacterial ability of magnesium alloy bone implants, with a broad antibacterial spectrum, which can reduce bacterial colonization in the prosthesis; at the same time, the dense rare earth oxide protective layer (Sc2O3 and Y2O3) formed under high-temperature oxidation heat treatment has a broad-spectrum antibacterial effect, which can effectively kill Staphylococcus aureus and Escherichia coli in vitro, and prevent orthopedic implant infection.

[0099] The final magnesium alloy bone implant was tested for its compression and tensile properties on a universal mechanical testing machine. The compression yield strength of the bone implant scaffold was 40MPa, the compression ultimate strength was 61MPa, and the Young's modulus was 6Gpa;

[0100] After 90 days of immersion in simulated body fluids in Hanks' solution, the bone implant sample was able to maintain its scaffold morphology without obvious cracks;

[0101] The in vitro antibacterial activity of the new magnesium alloy powder additive manufacturing implant and the traditional WE43 additive manufacturing magnesium alloy bone implant was compared by using the in vitro MRSA bacterial culture plate method. The sample extract was collected and co-cultured with 1×106 CFU / mL bacterial solution at 37° for 24 hours. The number of bacterial colonies on the TSA bacterial culture plate was counted and quantitatively analyzed. Figure 2 Shown are cell scratch images of the magnesium alloy bone implant of Example 1 and the bone implant formed by WE43 alloy under the same conditions after 0h and 24h. It can be seen from the figure that the magnesium alloy bone implant of Example 1 has better performance in promoting vascular endothelial cell migration.

[0102] Figure 3 The figure is a quantitative analysis diagram of the cell scratch migration ability of the magnesium alloy bone implant of Example 1 and the bone implant formed by WE43 alloy under the same conditions after 0h and 24h. It can be seen from the figure that the magnesium alloy bone implant of Example 1 has better performance in promoting angiogenesis.

[0103] Figure 4 The figure shows the bacteria and fungi of the magnesium alloy bone implant in Example 1 and the bone implant formed by WE43 alloy under the same conditions after 0h and 24h. It can be seen from the figure that the magnesium alloy bone implant in Example 1 has a stronger bactericidal ability against MRSA bacterial colonies than the bone implant formed by WE43 alloy.

[0104] Example 2

[0105] A medical magnesium rare earth alloy powder comprises the following components by weight: Sc: 2.75%, Zr: 0.4%, Y: 5%, and the remainder is Mg and unremovable impurity elements.

[0106] Prepared by the following steps:

[0107] Step 1: weigh pure metal ingots and / or high-purity alloy ingots according to the composition ratio of the magnesium alloy;

[0108] According to the composition ratio, Mg ingots, Mg-Zr ingots, Mg-30Sc ingots, and Mg-20Y ingots with a purity of more than 99.99% were weighed, with a total weight of 50 kg; including 0.85 kg of Mg-30Zr, 5 kg of Mg-30Sc, 15 kg of Mg-20Y, and 29.15 kg of Mg.

[0109] Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot;

[0110] Put the weighed Mg ingot, Mg-20Y master alloy, Mg-30Sc master alloy and Mg-Zr master alloy into the tantalum crucible of the vacuum medium frequency induction furnace and evacuate the furnace. When the vacuum degree is less than 1*10 -2 Pa, start heating and fill with high-purity argon as a protective atmosphere, heat at 800°C, keep warm for 12 min, stir the melt with a graphite stirring paddle at a stirring rate of 35 rpm / min; after complete melting, pour the melt evenly into a graphite mold preheated to 180°C at a pouring temperature of 850°C, and obtain an intermediate alloy ingot after cooling with the furnace.

[0111] Step 3: Detect the composition of the master alloy ingot to ensure that the content of impurity elements such as Fe, Cu, Ni, Co, Be, and Al is less than 100ppm, then pickle or mechanically polish to remove dirt or oxide layer on the surface of the master alloy ingot, and remelt the master alloy ingot at 780°C to obtain a master alloy ingot melt;

[0112] Step 4: The master alloy ingot melt is powdered by atomization to obtain pre-alloyed powder;

[0113] The atomization powder making method is argon atomization. Before atomization, the argon is dehydrated / dried and deoxygenated. Argon is protected by combined atomization and then introduced into the atomization chamber to ensure that the oxygen content and humidity of the environment in which the melt is atomized are both lower than 10ppm.

[0114] The atomization temperature is 830°C, the atomization pressure is 30KPa, the nozzle size is 10mm, and the atomization speed is 65000rpm / min.

[0115] Step 5: The pre-alloyed powder is sieved through 100 mesh and 250 mesh sieves to obtain a pre-alloyed powder with an average particle size of 65.7 μm and a nearly spherical or spherical shape;

[0116] The pre-alloyed powder was used in the additive manufacturing process and was formed into the shape of the bone implant by selective laser melting (SLM). The additive manufacturing parameters were: scanning power of 800 W, scanning speed of 500 mm / s, powder thickness of 22 μm, and scanning spacing of 80 μm. Before additive manufacturing, the substrate of the selective laser melting equipment was preheated at a preheating temperature of 220 °C.

[0117] The magnesium alloy bone implant obtained by additive manufacturing is subjected to an integrated high-temperature oxidation heat treatment to obtain a final magnesium alloy bone implant, wherein the integrated high-temperature oxidation heat treatment process comprises the following steps:

[0118] S1: After the finished product of additively manufactured magnesium alloy bone implant is cooled to room temperature, it is pickled;

[0119] After the finished additively manufactured magnesium alloy bone implant is cooled to room temperature, it is placed in a dissolving solution for pickling, and the entire pickling process is cooled in a water bath; wherein the dissolving solution includes a volume concentration of 10% HNO3, 10% HCl and 80% alcohol; and the pickling time is 3 minutes.

[0120] S2: After the pickling is completed, the finished product of the additively manufactured magnesium alloy bone implant is ultrasonically treated twice with alcohol to wash away the residual acid on the surface, and then placed in a drying oven for drying for 36 hours;

[0121] S3: After drying, the finished product of the additively manufactured magnesium alloy bone implant is placed in a muffle furnace for HTO treatment, with a thermal oxidation temperature of 500°C and a thermal oxidation time of 6 hours.

[0122] The final magnesium alloy bone implant was tested for its compression and tensile properties on a universal mechanical testing machine. The compression yield strength of the bone implant scaffold was 52MPa, the compression ultimate strength was 63MPa, and the Young's modulus was 6.5Gpa;

[0123] After 87 days of immersion in simulated body fluid in Hanks' solution, the bone implant sample was still able to maintain its scaffold morphology without obvious cracks.

[0124] Comparative Example 1

[0125] The medical magnesium rare earth alloy powder of this comparative example has the following components by weight percentage: Sc: 1.0%, Zr: 0.6%, Y: 2.5%, and the rest are Mg and unremovable impurity elements.

[0126] According to the composition ratio, Mg ingots, Mg-Zr ingots, Mg-30Sc ingots, and Mg-20Y ingots with a purity of more than 99.99% were weighed, with a total weight of 50 kg; including 0.85 kg of Mg-30Zr, 3.5 kg of Mg-30Sc, 15 kg of Mg-20Y, and 30.65 kg of Mg.

[0127] The remaining steps are the same as those in Example 1.

[0128] The final magnesium alloy bone implant was tested for its compression and tensile properties on a universal mechanical testing machine. The compression yield strength of the bone implant scaffold was 32MPa, the compression ultimate strength was 43MPa, and the Young's modulus was 4.2Gpa;

[0129] After 60 days of immersion in simulated body fluids in Hanks' solution, the bone implant sample was still able to maintain its scaffold morphology without obvious cracks. After 65 days, the scaffold degradation accelerated, and the structure collapsed around 70 days.

[0130] Comparative Example 2

[0131] The medical magnesium rare earth alloy powder of this comparative example has the same composition ratio as that of Example 2, except that:

[0132] Prepared by the following steps:

[0133] Step 1: weigh pure metal ingots and / or high-purity alloy ingots according to the composition ratio of the magnesium alloy;

[0134] According to the composition ratio, Mg ingots, Mg-Zr ingots, Mg-30Sc ingots, and Mg-20Y ingots with a purity of more than 99.99% were weighed, with a total weight of 50 kg; including 0.85 kg of Mg-30Zr, 5 kg of Mg-30Sc, 15 kg of Mg-20Y, and 29.15 kg of Mg.

[0135] Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot;

[0136] Put the weighed Mg ingot, Mg-20Y master alloy, Mg-30Sc master alloy and Mg-Zr master alloy into the tantalum crucible of the vacuum medium frequency induction furnace and evacuate the furnace. When the vacuum degree is less than 1*10 -2 Pa, start heating and fill with high-purity argon as a protective atmosphere, heat at 850°C, keep warm for 10 min, stir the melt with a graphite stirring paddle at a stirring rate of 25 rpm / min; after complete melting, pour the melt evenly into a graphite mold preheated to 130°C at a pouring temperature of 880°C, and obtain an intermediate alloy ingot after cooling with the furnace.

[0137] Step 3: Detect the composition of the master alloy ingot to ensure that the content of impurity elements such as Fe, Cu, Ni, Co, Be, and Al is less than 100ppm, then pickle or mechanically polish to remove dirt or oxide layer on the surface of the master alloy ingot, and remelt the master alloy ingot at 800°C to obtain a master alloy ingot melt;

[0138] Step 4: The master alloy ingot melt is powdered by atomization to obtain pre-alloyed powder;

[0139] The atomization powder making method is argon atomization. Before atomization, the argon is dehydrated / dried and deoxygenated. Argon is protected by combined atomization and then introduced into the atomization chamber to ensure that the oxygen content and humidity of the environment in which the melt is atomized are both lower than 10ppm.

[0140] The atomization temperature is 820°C, the atomization pressure is 25KPa, the nozzle size is 6mm, and the atomization speed is 50000rpm / min.

[0141] Step 5: The pre-alloyed powder is sieved through 100 mesh and 250 mesh sieves to obtain a pre-alloyed powder with an average particle size of 78.5 μm and a nearly spherical or spherical shape;

[0142] The pre-alloyed powder was used in the additive manufacturing process and was formed into the shape of the bone implant by selective laser melting (SLM). The additive manufacturing parameters were: scanning power of 500 W, scanning speed of 600 mm / s, powder thickness of 20 μm, and scanning spacing of 70 μm. Before additive manufacturing, the substrate of the selective laser melting equipment was preheated at 200 °C.

[0143] The magnesium alloy bone implant obtained by additive manufacturing is subjected to an integrated high-temperature oxidation heat treatment to obtain a final magnesium alloy bone implant, wherein the integrated high-temperature oxidation heat treatment process comprises the following steps:

[0144] S1: After the finished product of additively manufactured magnesium alloy bone implant is cooled to room temperature, it is pickled;

[0145] After the finished product of additively manufactured magnesium alloy bone implant is cooled to room temperature, it is placed in a dissolving solution for pickling, and the entire pickling process is cooled in a water bath; wherein the dissolving solution includes 5% HNO3, 5% HCl and 90% alcohol by volume; and the pickling time is 30s.

[0146] S2: After pickling, the finished product of the additively manufactured magnesium alloy bone implant is ultrasonically treated twice with alcohol to wash away the residual acid on the surface, and then placed in a drying oven for 48 hours;

[0147] S3: After drying, the finished product of the additively manufactured magnesium alloy bone implant is placed in a muffle furnace for HTO treatment, with a thermal oxidation temperature of 500°C and a thermal oxidation time of 4 h.

[0148] The final magnesium alloy bone implant was tested for its compression and tensile properties on a universal mechanical testing machine. The compression yield strength of the bone implant scaffold was 30MPa, the compression ultimate strength was 40MPa, and the Young's modulus was 4.8Gpa;

[0149] The bone implant sample was immersed in a simulated body fluid in Hanks' solution for 10 days and still maintained its scaffold morphology, but lost its scaffold morphology after 15 days.

[0150] Comparative Example 3

[0151] The medical magnesium rare earth alloy powder of this comparative example has the following components by weight percentage: Sc: 2.75%, Zr: 0.4%, Y: 2.1%, and the rest are Mg and unremovable impurity elements.

[0152] Prepared by the following steps:

[0153] Step 1: weigh pure metal ingots and / or high-purity alloy ingots according to the composition ratio of the magnesium alloy;

[0154] According to the composition ratio, Mg ingots, Mg-Zr ingots, Mg-30Sc ingots, and Mg-20Y ingots with a purity of more than 99.99% were weighed, with a total weight of 50 kg; including Mg-30Zr: 1.75 kg, Mg-30Sc: 10 kg, Mg-20Y: 10 kg, and Mg: 28.25 kg.

[0155] Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot;

[0156] Put the weighed Mg ingot, Mg-20Y master alloy, Mg-30Sc master alloy and Mg-Zr master alloy into the tantalum crucible of the vacuum medium frequency induction furnace and evacuate the furnace. When the vacuum degree is less than 1*10 -2 Pa, start heating and fill with high-purity argon as a protective atmosphere, heat at 800°C, keep warm for 12 min, stir the melt with a graphite stirring paddle at a stirring rate of 35 rpm / min; after complete melting, pour the melt evenly into a graphite mold preheated to 180°C at a pouring temperature of 850°C, and obtain an intermediate alloy ingot after cooling with the furnace.

[0157] Step 3: Detect the composition of the master alloy ingot to ensure that the content of impurity elements such as Fe, Cu, Ni, Co, Be, and Al is less than 100ppm, then pickle or mechanically polish to remove dirt or oxide layer on the surface of the master alloy ingot, and remelt the master alloy ingot at 780°C to obtain a master alloy ingot melt;

[0158] Step 4: The master alloy ingot melt is powdered by atomization to obtain pre-alloyed powder;

[0159] The atomization powder making adopts the centrifugal atomization method. Before atomization, the argon gas is dehydrated / dried and deoxygenated, wherein: the argon gas is protected by the combined atomization and then introduced into the atomization chamber to ensure that the oxygen content and humidity of the environment in which the melt is atomized are both lower than 10ppm;

[0160] The atomization temperature is 800°C, the atomization pressure is 30KPa, the nozzle size is 6mm, and the atomization speed is 50000rpm / min.

[0161] Step 5: The pre-alloyed powder is sieved through 100 mesh and 250 mesh sieves to obtain a pre-alloyed powder with an average particle size of 72 μm and a nearly spherical or spherical shape;

[0162] The pre-alloyed powder was used in the additive manufacturing process, and the pre-alloyed powder was formed into the shape of the bone implant by selective laser melting (SLM). In the additive manufacturing process, the powder bed and the magnesium alloy powder matrix were first preheated at 150 ° C for 1 hour, and then SLM was performed. The working chamber was filled with argon and oxygen was controlled below 500 ppm; the processing parameters used were as follows: laser power 80 W, scanning speed 450 mm / s, layer thickness 20 μm, and filling spacing 70 μm.

[0163] The magnesium alloy bone implants obtained by additive manufacturing were subjected to micro-arc oxidation surface treatment.

[0164] The bone implant scaffold has a compressive yield strength of 28MPa, a compressive ultimate strength of 40MPa, and a Young's modulus of 5Gpa;

[0165] After 60 days of immersion in simulated body fluids in Hanks' solution, the bone implant sample was still able to maintain its morphology, but there were obvious cracks on the surface of the scaffold.

[0166] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A medical bone implant material, characterized in that: The components are calculated by weight percentage: Sc: 2.25-2.75%, Zr: 0.4-0.5%, Y: 4-5%, and the rest is Mg and impurity elements that cannot be removed, obtained by additive manufacturing and high-temperature oxidation heat treatment of medical magnesium rare earth alloy powder. The high temperature oxidation heat treatment comprises: S1: Additively manufactured magnesium alloy bone implant material cooled to room temperature and pickled; S2: After pickling, ultrasonic cleaning is performed to remove residual acid on the surface, followed by drying for 24h-48h; S3: After drying, HTO treatment is performed, the thermal oxidation temperature is 500-530°C, and the thermal oxidation time is 6-18h.

2. The medical bone implant material according to claim 1, characterized in that: The preparation method of the medical magnesium rare earth alloy powder comprises: Step 1: weighing pure metal ingots and / or high-purity alloy ingots according to the magnesium alloy composition ratio, wherein the pure metal ingot is a Mg ingot, and the high-purity alloy ingot includes a Mg-Y master alloy, a Mg-Sc master alloy, and a Mg-Zr master alloy; Step 2: obtaining a master alloy ingot by vacuum melting a pure metal ingot and / or a high-purity alloy ingot; Step 3: Detect the composition of the master alloy ingot, remove dirt or oxide layer on the surface of the master alloy ingot by pickling or mechanical grinding, and remelt the master alloy ingot again to obtain a master alloy ingot melt; Step 4: atomizing the master alloy ingot melt to obtain a first pre-alloyed powder; Step 5: Sieve the first pre-alloyed powder through a sieve to obtain a second pre-alloyed powder that meets the size and shape requirements; Step 6: vacuum drying the second pre-alloyed powder to obtain magnesium alloy powder, and vacuum packaging it.

3. The medical bone implant material according to claim 2, characterized in that: In step 2, during the vacuum melting process, the heating temperature is 750-800° C., the holding time is 8-12 min, and the stirring rate is 30-35 r / min.

4. The medical bone implant material according to claim 3, characterized in that: In step 3, the remelting temperature is 700-800°C.

5. The medical bone implant material according to claim 4, characterized in that: In step 4, the atomization powder making is an argon protection combined atomization method, the atomization temperature is 750-800° C., the atomization pressure is 30-50 kPa, the nozzle size is 5-10 mm, and the atomizer speed is 55000-65000 r / min.

6. The medical bone implant material according to claim 1, characterized in that: The additive manufacturing is selective laser melting, and the parameters are: scanning power is 600-800W, scanning speed is 500-600mm / s, powder thickness is 18-22μm, and scanning spacing is 60-80μm.

Citation Information

Patent Citations

  • Magnesium alloy powder for additive manufacturing and preparation method and application thereof

    CN113564439A

  • Magnesium alloy medical implant and preparation method thereof

    CN114288471A

  • Mg-Zn-Sc-Mn magnesium alloy material and preparation method thereof

    CN117026041A

Cited By

  • Method for preparing 316L stainless steel through selective laser melting and rare earth alloy powder adding

    CN120505554A

  • Method for preparing high-performance rare earth magnesium-silicon-iron alloy through cooperation of pulsed magnetic field treatment and multi-element microalloying

    CN122038815A